A sportification model of the traditional Singkongan game: Development and content validation of Singkoball - Pratama, Dhiya Ulhaq Oksa; Khampoosa, Panita; Anggita, Gustiana Mega (UIR Press, 2026)
Background: The lack of standardised rules and safety measures in traditional games limits their utility for structured physical activity and fitness promotion. In particular, the traditional Singkongan game, which involves wooden sticks, presents safety risks and diminishes its suitability for modern fitness contexts. Objectives: This study aimed to develop and examine the content validity of Singkoball as a sportified model of the traditional Singkongan game. Methods: A research and development design was employed, focusing on product development and expert validation. Four experts (two sports specialists, one linguist, and one graphic design expert) evaluated the product using structured validation instruments. Data were analysed using percentage-based validity criteria and inter-rater agreement. Results: The developed product demonstrated high content validity, with valid scores of 98.96% (sports experts), 88.90% (language experts), and 88.60% (design experts), resulting in an overall score of 92.15%. These findings indicate a high level of agreement regarding the clarity, safety, and usability of the developed model. Conclusion: Singkoball demonstrates robust content validity and feasibility as a culture-based model. However, its impact on motor skill development and engagement among children and adolescents has yet to be empirically established and requires rigorous field-based evaluation.